Substantial Justice In Handling Of Child Actors "Klitih" - Adi Wibowo; Umar Ma’ruf (Jurnal Daulat Hukum, 2019)
"Klitih" has become a negative label of the last few years in the area DIY. Lebel is pinned to the perpetrators of criminal acts of persecution accompanied by vandalism committed by children, the widespread and massive occur within this period and led to loss of life and property. Act No. 11 of 2012 on the Criminal Justice System of Children who are formally to be done by the Regional Police of Yogyakarta in the treatment of perpetrators of maltreatment ("klitih"), has not given the benefit and sense of justice to the people. This happens because the concept of juvenile criminal justice system does not provide a deterrent effect to the child as a criminal offender. The pattern of interaction of children is also one of the causes of delinquency,In the juvenile criminal justice system, there is the concept of restorative justice should be applied at the beginning of the judicial system (investigation), in order to provide protection (special treatment) for children in conflict with the law so as not to disturb or shut off the child's development. It is true that the protection obtained by children in conflict with the law (especially actors), but it is different for the victim and the community, not necessarily the effect of juvenile criminal justice system can provide substantial protection and justice for him.Keywords: Children, Klitih, Juvenile Justice System, Substantial Justice.